2020
DOI: 10.3390/cells9112497
|View full text |Cite
|
Sign up to set email alerts
|

Perspective on Schwann Cells Derived from Induced Pluripotent Stem Cells in Peripheral Nerve Tissue Engineering

Abstract: Schwann cells play a crucial role in successful peripheral nerve repair and regeneration by supporting both axonal growth and myelination. Schwann cells are therefore a feasible option for cell therapy treatment of peripheral nerve injury. However, sourcing human Schwann cells at quantities required for development beyond research is challenging. Due to their availability, rapid in vitro expansion, survival, and integration within the host tissue, stem cells have attracted considerable attention as candidate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 96 publications
1
37
0
Order By: Relevance
“…In view of the fact that optimized axonal regeneration crucially depends on the invasion of the bioartificial grafts by e.g., repair Schwann cells [ 18 , 19 , 26 , 30 ], perineurial fibroblasts [ 36 ], or pro-regenerative cells from the immune system [ 14 , 37 , 38 ], it is also important to consider the interaction of the provided bioartificial graft with regeneration supporting cells types. It was recently demonstrated that collagen-based nerve guides with an optimized internal 3D structure could be enriched with autologous Schwann cells for improving regeneration of an acutely repaired 13 mm sciatic nerve defect in the rat [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In view of the fact that optimized axonal regeneration crucially depends on the invasion of the bioartificial grafts by e.g., repair Schwann cells [ 18 , 19 , 26 , 30 ], perineurial fibroblasts [ 36 ], or pro-regenerative cells from the immune system [ 14 , 37 , 38 ], it is also important to consider the interaction of the provided bioartificial graft with regeneration supporting cells types. It was recently demonstrated that collagen-based nerve guides with an optimized internal 3D structure could be enriched with autologous Schwann cells for improving regeneration of an acutely repaired 13 mm sciatic nerve defect in the rat [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Especially the well-orchestrated interplay between the different cell types is crucial for an optimized support of axonal regeneration [ 37 ]. Schwann cells (SC) from the repair phenotype play the most crucial, centralized role in successful peripheral nerve regeneration [ 18 , 19 , 26 ]. After injury, Schwann cells secrete cytokines and interleukins, while myelin expression is inhibited for the time of early axonal outgrowth by the expression of the transcription factor Sox2 [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This aligns with in vitro data that showed Schwann cells elongated to a greater extent on fibronectin compared to laminin ( Gonzalez-Perez et al, 2017 , 2018 ), indicating that Schwann cell elongation is associated with positive effects on neuron growth. Stem cells have been widely used either directly in peripheral nerve guidance constructs or differentiated into Schwann cell-like cells with promising results ( Ziegler et al, 2011 ; Martens et al, 2014 ; Georgiou et al, 2015 ; Sakaue and Sieber-Blum, 2015 ; Jung et al, 2016 ; Cai et al, 2017 ; Huang et al, 2017 , 2020 ; Kim et al, 2017 ; Sanen et al, 2017 ; Jones et al, 2018 ; Kubiak et al, 2020 ). However, it is not known in these cases if these differentiated cells will behave comparably in response to different biomaterials to the Schwann cells found in a native injury environment.…”
Section: The Addition Of Laminin or Fibronectin And Certain Peptides Can Improve Functional Outcomesmentioning
confidence: 99%
“…Lastly, hSCs can be generated in vitro from embryonic and induced pluripotent stem cells via stepwise differentiation, or from somatic cells such as fibroblasts via transdifferentiation or direct conversion (reviewed in Huang et al, 2020). SC-like cells prepared from bone marrow-or adipose tissue-derived mesenchymal stem cells offer promise for autologous therapies to repair damage in SCI and other forms of nervous system trauma (Hopf et al, 2020).…”
Section: Types Of Transplantable Hscsmentioning
confidence: 99%